2002
DOI: 10.1097/00005176-200210000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Interleukin-2 Receptor, Interleukin-6, and Tumor Necrosis Factor-α Levels in Children with Celiac Disease: Response to Treatment

Abstract: The serum soluble interleukin-2 receptor and interleukin-6 levels may be used as a noninvasive measure of celiac disease activity and response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
32
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
8
32
1
Order By: Relevance
“…Our results are according with those of Tau et al (6), Pantaleoni et al (7) and Di Stefano et al (8). With the GFD, the levels of interleukin-6, but not of TNF-α, decrease (26). Results regarding parathyroid function in treated celiac patients show that they are similar to control group excluding a residual secondary hyperparathyroidism (27).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are according with those of Tau et al (6), Pantaleoni et al (7) and Di Stefano et al (8). With the GFD, the levels of interleukin-6, but not of TNF-α, decrease (26). Results regarding parathyroid function in treated celiac patients show that they are similar to control group excluding a residual secondary hyperparathyroidism (27).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, mean serum levels of inflammatory cytokines that contribute to ACD, including interleukin-1β, interleukin-6, tumor necrosis factor-α, and interferon-γ, are increased in active celiac disease. [24][25][26][27] Our results hint at a defective production of endogenous erythropoietin, in addition to changes in iron homeostasis, as a pathogenetic mechanism of ACD. A defective production of erythropoietin for the degree of anemia has been reported in some studies on ACD, [28][29][30] although adequate erythropoietin levels were observed in ACD subjects with systemic juvenile chronic arthritis.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have shown that intestinal inflammation in CD is due to different cytokines produced by CD4 T cells and that these are responsible for the pathogenesis of the disease (5,25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cytokines expressed by Th cells in the intestinal mucosa in CD, the production of macrophage-origin IL-6 has been determined to increase and play a role in intestinal inflammation (5,25). Studies have reported a relation between the IL-6 (-572G/C) polymorphism and high serum IL-6 (9).…”
Section: Discussionmentioning
confidence: 99%